The Contribution of Different Components in QiShenYiQi Pills® to Its Potential to Modulate Energy Metabolism in Protection of Ischemic Myocardial Injury - Cui, Yuan-Chen; Yan, Li; Pan, Chun-Shui; Hu, Bai-He; Chang, Xin; Fan, Jing-Yu; Han, Jing-Yan (Frontiers in Physiology, 2018)
Ischemic heart diseases remain a challenge for clinicians. QiShenYiQi pills® (QSYQ) has been reported to be curative during coronary heart diseases with modulation of energy metabolism as one of the underlying mechanisms. In this study, we detected the effect of QSYQ and its components on rat myocardial structure, mitochondrial respiratory chain complexes activity and energy metabolism, and heart function after 30 min of cardiac ischemia, with focusing on the contribution of each component to its potential to regulate energy metabolism. Results showed that treatment with QSYQ and all its five components protected myocardial structure from damage by ischemia. QSYQ also attenuated release of myocardial cTnI, and restored the production of ATP after cardiac ischemia. AS-IV and Rb1, but not Rg1, R1, and DLA, had similar effect as QSYQ in regulation of energy metabolism. These results indicate that QSYQ may prevent ischemia-induced cardiac injury via regulation of energy metabolism, to which each of its components contributes differently.